Pesquisa de Rickettsia spp em carrapatos Amblyomma cajennense e Amblyomma dubitatum no Estado de São Paulo Survey of Rickettsia spp in the ticks Amblyomma cajennense and Amblyomma dubitatum in the State of São Paulo - Richard Campos Pacheco; Maurício Cláudio Horta; Adriano Pinter; Jonas Moraes-Filho; Thiago Fernandes Martins; Marcello Schiavo Nardi; Savina Silvana Aparecida Lacerra de Souza; Celso Eduardo de Souza; Matias Pablo Juan Szabó; Leonardo José Richtzenhain; Marcelo Bahia Labruna (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
Foi pesquisada a presença de riquétsias em 3.545 carrapatos Amblyomma cajennense e 2.666 Amblyomma dubitatum. Através do teste de hemolinfa, reação em cadeia pela polimerase e isolamento de rickettsia em cultivo celular, todos os Amblyomma cajennense foram negativos, sendo que 634 (23,8%) Amblyomma dubitatum mostraram-se infectados com Rickettsia bellii. The presence of rickettsial infection was surveyed in 3,545 Amblyomma cajennense ticks and 2,666 Amblyomma dubitatum ticks. Using the hemolymph test, polymerase chain reaction and isolation of Rickettsia in cell cultures, all of the Amblyomma cajennense were negative, whereas 634 (23.8%) of the Amblyomma dubitatum ticks were shown to be infected with Rickettsia bellii.